Interrater variability for CT angiography evaluation between neurologists and neuroradiologist in acute stroke patients - Bar, Michal; Kral, Jiri; Jonszta, Tomas; Marcian, Vaclav; Kuliha, Martin; Mikulik, Robert (The British journal of radiology, 2017)
OBJECTIVE: The diagnosis of arterial occlusion has a considerable impact on the indication of mechanical thrombectomy, and CT angiography (CTA) is recommended in the management of acute stroke. The goal of the present study is to assess the interrater agreement in the diagnosis of occlusion of intracranial arteries on CTA between a neuroradiologist and neurologists. METHODS: CTA images of 75 acute stroke patients were evaluated for occlusion of intracranial arteries by an experienced interventional neuroradiologist, and stroke and general neurologists. RESULTS: 75 patients who were treated by intravenous thrombolysis were enrolled in the study. CTA images were available for all 75 patients (34 females; mean age ± SD, 72 ± 14 years; National Institutes of Health Stroke Scale 10; median 8-14; and Alberta Stroke Program Early CT mean 9.7). The agreement between the neuroradiologist and neurologists in evaluation of intracranial artery occlusion was as follows: occlusion of the middle cerebral artery segment M1: observer agreement 77%, kappa (κ) = 0.61 and middle cerebral artery M2: observer agreement 77%, κ 0.48; internal carotid artery: observer agreement 92%, κ 0.84; T occlusion: observer agreement 90.0%, κ 0.33; posterior cerebral artery segments P1 and P2: observer agreement 98%, κ 0.97; basilar artery: observer agreement 96%, κ 0.92; and vertebral artery segment V4: observer agreement 88%, κ 0.48. CONCLUSION: Interrater agreement of CTA evaluation of occlusion between the neurologists and the neuroradiologist was very strong. The ability of the trained neurologists to read an intracranial large vessel occlusion correctly may improve the door-to-needle times in acute stroke. Advances in knowledge: In this study, the neurologists were able to recognize occlusion of intracranial arteries. This could accelerate the management of acute stroke care.
Keywords: Neurologists; mozek; Humans; Stroke; Female; Aged; senioři; lidé; Computed Tomography Angiography; Cerebral Angiography; reprodukovatelnost výsledků; cévní mozková příhoda; mozková angiografie; ženské pohlaví; Neuroradiography; Male; Reproducibility of Results; Brain; neuroradiografie; odchylka pozorovatele; Observer Variation; mužské pohlaví; CT angiografie; neurologové